2018
DOI: 10.1590/s1517-707620180002.0545
|View full text |Cite
|
Sign up to set email alerts
|

Materiales eco-compatibles reforzados a base de almidón de mandioca para aplicaciones agronómicas

Abstract: RESUMEN La utilización de plásticos de cobertura o mulching en diversos cultivos puede aumentar los rendimientos, extender la temporada de crecimiento, controlar malezas, aumentar la eficiencia de los fertilizantes y mejorar las condiciones del suelo. Sin embargo, luego de su uso son fuente de contaminación ambiental y su remoción genera un costo adicional. Para este fin y otras aplicaciones de interés agronómico el uso de películas a base de almidón es una alternativa viable debido a su biodegradabilidad, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This effect was also reported by [24] when working with arracacha starch with 66% solubility, also [25] found the values of solubility between 68 and 80% when working with potato starch, glycerol, and acetic acid. Others researchers [26] reported that high solubility, over 60% when working with cassava starch and fiber, decreased with the increment of fiber added, resulting in degradation from day 25 when working under controlled conditions.…”
Section: A Solubility In Watermentioning
confidence: 96%
“…This effect was also reported by [24] when working with arracacha starch with 66% solubility, also [25] found the values of solubility between 68 and 80% when working with potato starch, glycerol, and acetic acid. Others researchers [26] reported that high solubility, over 60% when working with cassava starch and fiber, decreased with the increment of fiber added, resulting in degradation from day 25 when working under controlled conditions.…”
Section: A Solubility In Watermentioning
confidence: 96%
“…The latter has derived considerable research, development and commercialization of novel biodegradable, and biobased mulch films, that at the end of their lifetime degrade and mineralize in soil avoiding recollection and acting as in situ soil fertilizer [1,246,441,442]. Various oil-based and biobased biodegradable polymer films and their blends and copolymers have been studied as mulch films [120,435,[443][444][445]. Field studies have also been performed on commercial biodegradable bioplastics [434,436], yet biodegradation rate is clearly dependent not only on bioplastic nature but also on climate conditions and soil characteristics.…”
Section: Biobased Composites As Fertilizer Delivery and Their Applications As Agricultural Inputsmentioning
confidence: 99%